A CHAPTER'S DEVELOVMENT STUDY IN A WALK TO REMEMBER AS BILDUNGSROMAN - Lidya Cristina Situmorang, - (2010)
ABSTRACT The study investigates the main character development in A Walk to Remember. This textual analysis study used characterization and focalization theories serving the research questions answers. The study found that the main character development is constructed through several events, which are joining, practicing, and performing a play, celebrating Christmas at orphanage, knowing that Jamie was dying, and marrying Jamie. The study concludes that there are events in life, which could encourage people to change. Of these events there might be an event serving as the turning point. The ways people struggle toward the events signify the change in their life.